Patient and Parent Well-Being and Satisfaction With Diabetes Care During a Comparative Trial of Mobile Self-Monitoring Blood Glucose Technology and Family-Centered Goal Setting - Halper, Jillian B.; Yazel, Lisa G.; El Mikati, Hala; Hatton, Amy; Tully, Jennifer; Li, Xiaochun; Carroll, Aaron E.; Hannon, Tamara S. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Patient engagement in the process of developing a diabetes treatment plan is associated with person-centered care and improved treatment outcomes. The objective of the present study was to evaluate the self-reported patient and parent-centered satisfaction and well-being outcomes associated with the three treatment strategies utilized in a comparative effectiveness trial of technology-enhanced blood glucose monitoring and family-centered goal setting. We evaluated data from 97 adolescent-parent pairs at baseline and 6-months during the randomized intervention. Measures included: Problem Areas in Diabetes (PAID) child and parent scales, pediatric diabetes-related quality of life, sleep quality, and satisfaction with diabetes management. Inclusion criteria were 1) ages 12-18 years, 2) a T1D diagnosis for at least six months and 3) parent/caregiver participation. Longitudinal changes in survey responses were measured at 6 months from baseline. Differences between and within participant groups were evaluated using ANOVA. The average age of youth participants was 14.8 ± 1.6 years with half of the participants being female (49.5%). The predominant ethnicity/race was Non-Hispanic (89.9%) and white (85.9%). We found that youth perceived 1) greater of diabetes-related communication when using a meter capable of transmitting data electronically, 2) increased engagement with diabetes self-management when using family-centered goal setting, and 3) worse sleep quality when using both strategies together (technology-enhanced meter and family-centered goal setting). Throughout the study, scores for self-reported satisfaction with diabetes management were higher in youth than parents. This suggests that patients and parents have different goals and expectations regarding their diabetes care management and care delivery. Our data suggest that youth with diabetes value communication via technology and patient-centered goal setting. Strategies to align youth and parent expectations with the goal of improving satisfaction could be utilized as a strategy to improve partnerships in diabetes care management.